Cyberjaya, Malaysia: Bridging the Gap Between User Acceptance and the 5G Technology Readiness - Tasmin, Rosmaini; Lim, Jea Yi; Abu Bakar, Suwaibah (Research in Management of Technology and Business, 2023)
5G technology is the fifth generation of mobile networks inspired by the4.0 Industrial Revolution's expanding capacity requirements for increased speed,broad coverage, and reliable security. It is much more than a fast mobile internetconnection that allows for the consumption of copious amounts of data-based content.The primary concern of 5G in this study is the second-lowest download speed of 13.5Mbps after the launch of 5G in Malaysia. This issue may affect user readiness andacceptance of 5G technology.The primary purpose is to identify the variables that influence user acceptance of 5Gtechnology readiness in Cyberjaya. This study employed a quantitative methodologyto collect secondary data from related publications. Via a quantitative researchmethodology, data were gathered from 382 members of the target population using aweb-based survey questionnaire. To meet the aims of this research, descriptivestatistics analysis and inferential statistics analysis are utilised to analyse the data. Thestudy reveals the aspects that determine the 5G technology readiness of users. Inaddition, the study revealed that elements of user approval such as PerformanceExpectation, Effort Expectation, and Social Influence exist. The inability togeneralise the findings to different mobile networks was one of the constraints of thisstudy. Therefore, it was suggested that future researchers examine several forms ofmobile networks to better comprehend the topic. This study's findings can lead to agreater comprehension of the viewpoints on user acceptance of 5G technology.